2005
DOI: 10.1522/24613872
|View full text |Cite
|
Sign up to set email alerts
|

rapport à l'institution scolaire chez de jeunes amérindiens en fin de formation secondaire :

Abstract: Le rapport à l'institution scolaire chez de jeunes amérindiens en fin de formation secondaire : Contribution à la compréhension du cheminement scolaire chez les Autochtones THÈSE PRÉSENTÉE COMME EXIGENCE PARTIELLE DU DOCTORAT EN ÉDUCATION PAR ROBERTO GAUTHIER AVRIL 2005 Mise en garde/AdviceAfin de rendre accessible au plus grand nombre le résultat des travaux de recherche menés par ses étudiants gradués et dans l'esprit des règles qui régissent le dépôt et la diffusion des mémoires et thèses produits dans cett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…When rubber prices reached twenty francs per kilo in 1910, one official observed that people abandoned other economic activities and devoted themselves to rubber collecting ' almost exclusively '. 99 As early as 1905, local juula passing through rural areas of Upper Guinée traded rice for rubber, and in 1907 the district of Kankan imported rice and millet from neighboring districts. 100 In 1911, one administrator lamented the fact that in Kankan, long the ' rice granary of the Soudan ', people now avoided rice cultivation because the rubber commerce 'lets them live in agreeable and easy comfort ' without working in the fields.…”
Section: R U B B E R S O C I a L M O B I L I T Y A N D C H A N G Ementioning
confidence: 99%
“…When rubber prices reached twenty francs per kilo in 1910, one official observed that people abandoned other economic activities and devoted themselves to rubber collecting ' almost exclusively '. 99 As early as 1905, local juula passing through rural areas of Upper Guinée traded rice for rubber, and in 1907 the district of Kankan imported rice and millet from neighboring districts. 100 In 1911, one administrator lamented the fact that in Kankan, long the ' rice granary of the Soudan ', people now avoided rice cultivation because the rubber commerce 'lets them live in agreeable and easy comfort ' without working in the fields.…”
Section: R U B B E R S O C I a L M O B I L I T Y A N D C H A N G Ementioning
confidence: 99%